Pengaruh Saluran Pemasaran Terhadap Harga Beras di Desa Sindang Kasih Kecamatan Ranomeeto Barat Kabupaten Konawe Selatan - Budi, Slamet Setya; Surni, Surni; Gafaruddin, Abdul (Department of Agribusiness, Halu Oleo University, 2018)
The purpose of this research is to know the marketing channel in Sindang Kasih Village, secondly to know the influence of marketing channel to rice price in Sindang Kasih Village, West Ranomeeto District, South Konawe Regency. The analysis used in this research is Simple Linear Regression Analysis. The result of this research shows that marketing channel in Sindang Kasih Village There are 2 marketing channels that is first Farmer - Grinder - Merchant - Consumer and second is Farmer - Grinder - consumer, Here are two marketing channels used for Rice distribution from farmer to consumer. There is a significant influence of marketing channel variables (X) and rice price variables (Y). This is evidenced by the results of t test calculation of 3.912, while ttable is 1.304 at the level of significance of 10% which means that Ha is accepted. It also obtained regression equation Y = 0,824 + 1,011X. In other words accept Ha namely: There is Influence of Marketing Channel Against the price of rice in Sindang Kasih Village, West Ranomeeto District, South Konawe Regency, and reject Ho, that is No Effect of Marketing Channel on rice price in Sindang Kasih Village, West Ranomeeto District, South Konawe Regency.